Aminophylline Induces Two Types of Arrhythmic Events in Human Pluripotent Stem Cell–Derived Cardiomyocytes - Klimovic, Simon; Scurek, Martin; Pesl, Martin; Beckerova, Deborah; Jelinkova, Sarka; Urban, Tomas; Kabanov, Daniil; Starek, Zdenek; Bebarova, Marketa; Pribyl, Jan; Rotrekl, Vladimir; Brat, Kristian (Frontiers in Pharmacology, 2022)
Cardiac side effects of some pulmonary drugs are observed in clinical practice. Aminophylline, a methylxanthine bronchodilator with documented proarrhythmic action, may serve as an example. Data on the action of aminophylline on cardiac cell electrophysiology and contractility are not available. Hence, this study was focused on analysis of changes in the beat rate and contraction force of human pluripotent stem cell-derived cardiomyocytes (hPSC-CM) and HL-1 cardiomyocytes in the presence of increasing concentrations of aminophylline (10 uM to 10 mM in hPSC-CM and 8 to 512 uM in HL-1 cardiomyocytes). Basic biomedical parameters, namely the beat rate (BR) and contraction force, were assessed in hPSC-CM using the atomic force microscopy (AFM). The beat rate changes under aminophylline were also examined on HL-1 cardiac muscle cell line via multielectrode array (MEA). Additionally, calcium imaging was used to evaluate the effect of aminophylline on intracellular Ca2+ dynamics in HL-1 cardiomyocytes. BR was significantly increased after application of aminophylline both in hPSC-CM (at 10 mM aminophylline) and in HL-1 cardiomyocytes (at 256 and 512 µM aminophylline) in comparison with control. A significant increase of the contraction force was also observed in hPSC-CM at 10 µM aminophylline (similar trend was visible at higher concentrations as well). Occurrence of the calcium sparks in HL-1 cardiomyocytes was significantly increased with the presence of 512 uM aminophylline. We conclude that the observed aberrant cardiomyocyte response to aminophylline suggests an arrhythmogenic potential of the drug. The acquired data represent a missing link between the arrhythmic events related to the aminophylline/theophylline treatment in clinical practice and describe cellular mechanisms of methylxanthine arrhythmogenesis. AFM combined with hPSC-CM may serve as a robust platform for direct drug effects screening.